Adapting roughages varying in quality and curing processes to the nutrition of beef cattle. A comparison of alfalfa silage and alfalfa hay; prairie hay and corn cobs; a special supplement vs. corn and soybean oilmeal. - Smith, E.F.; Richardson, D.; Cathcart, R.B.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
The Hereford heifers used in this test were of good to choice quality from the Brite Ranch at Marfa, Texas. They were delivered to Manhattan, Kansas, November 3, 1952, at a cost of 23 cents per pound. From that date until started on test December 22, 1952, they were fed prairie hay and 1 pound of soybean pellets per head daily. The first cutting alfalfa fed to Lots 1, 2, and 3 came from the same field. No preservative was used in making the silage. The wilted alfalfa was left in the field from 30 minutes to 3 hours. The non-wilted was cut, raked, picked up with H silage cutter, and hauled to the silo as rapidly as possible. The special supplement fed to Lot 5 at the rate of 3 pounds per head daily was of the following; composition: soybean oilmeal, 2.25 pounds; molasses, 0.50 pound; steamed bonemeal, 0.18 pound; salt, 0.06 pound; vitamin supplement, 0.01 pound (2,250 A and 400 D per gram).
Keywords: Beef; Quality; Curing; Alfalfa; Prairie hay; Soybean oil